Unsteady axisymmetric flow and heat transfer of a hybrid nanofluid over a permeable stretching/ shrinking disc - Khashi'ie, Najiyah Safwa; Md. Arifin, Norihan; Pop, Ioan (Emerald, 2021)
Purpose: This study aims to analyze the unsteady flow of hybrid Cu-Al2O3/water nanofluid over a permeable stretching/shrinking disc. The analysis of flow stability is also purposed because of the non-uniqueness of solutions. Design/methodology/approach: The reduced differential equations (similarity) are solved numerically using the aid of bvp4c solver (Matlab). Two types of thermophysical correlations for hybrid nanofluid (Type 1 and 2) are adopted for the comparison results. Using correlation Type 1, the heat transfer and flow analysis including the profiles (velocity and temperature) are presented in the figures and tables with different values control parameters. Three sets of hybrid nanofluid are analyzed: Set 1 (1% Al2O3 + 1% Cu), Set 2 (0.5% Al2O3 + 1% Cu) and Set 3 (1% Al2O3 + 0.5% Cu). Findings: The comparison of numerical values between present (Types 1 and 2 correlations) and previous (Type 2 correlations) results are in a good compliance with approximate percent relative error. The appearance of two solutions is noticed when the suction parameter is considered and the unsteady parameter is less than 0 (decelerating flow) for both stretching and shrinking disc while only one solution is possible for steady flow. The hybrid nanofluid in Set 1 can delay the separation of boundary layer but the hybrid nanofluid in Set 3 has the greatest heat transfer rate. Moreover, the inclusion of wall mass suction for stretching case can generate a significant increment of heat transfer rate approximately 90% for all fluids (water, single and hybrid nanofluids). Originality/value: The present findings are novel and can be a reference point to other researchers to further analyze the heat transfer performance and stability of the working fluids.